2017
DOI: 10.1016/j.otsr.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular block associated with supraclavicular block: An alternative to isolated interscalene block for analgesia in shoulder instability surgery?

Abstract: NCT identifier: NCT02397330.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…In contrast, the subscapular nerve is now recognized as a major contributor to the anterior superior quadrant of the shoulder joint, while the axillary nerve innervates the inferior half of the joint. 12 This realization of the limited analgesic role of the posterior suprascapular block has prompted researchers to investigate supplementary blocks, such as supraclavicular 46 and infraclavicular 47 blocks, to combine with the posterior suprascapular block to match the analgesic effect of interscalene block. A superior trunk block per se may also be an option, but its proximity to the phrenic nerve and lack of knowledge of its respiratory effects favor more distal alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the subscapular nerve is now recognized as a major contributor to the anterior superior quadrant of the shoulder joint, while the axillary nerve innervates the inferior half of the joint. 12 This realization of the limited analgesic role of the posterior suprascapular block has prompted researchers to investigate supplementary blocks, such as supraclavicular 46 and infraclavicular 47 blocks, to combine with the posterior suprascapular block to match the analgesic effect of interscalene block. A superior trunk block per se may also be an option, but its proximity to the phrenic nerve and lack of knowledge of its respiratory effects favor more distal alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 One new study showed that the US-guided supraclavicular block, combined with a suprascapular block, was an effective alternative to the interscalene block for postoperative analgesia after shoulder instability surgery. 15 Recently, subsequent to the report by Cornish 19 about the spreading of a local anesthetic between interscalene muscles during USguided SCBB, a prospective study 12 confirmed that sole US-guided SCBB was as effective as US-guided ISBB for shoulder arthroscopy. A suprascapular nerve crosses deep in the omohyoid muscle in the supraclavicular region.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, numerous alternative techniques have been investigated, but have been found to be nonequivalent analgesic methods when compared with ISBB . One new study showed that the US‐guided supraclavicular block, combined with a suprascapular block, was an effective alternative to the interscalene block for postoperative analgesia after shoulder instability surgery . Recently, subsequent to the report by Cornish about the spreading of a local anesthetic between interscalene muscles during US‐guided SCBB, a prospective study confirmed that sole US‐guided SCBB was as effective as US‐guided ISBB for shoulder arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations